(untitled) (Clinics, 2008)
OBJECTIVES: This study aimed to assess the impact of the duration of organ dysfunction on the outcome of patients with severe sepsis or septic shock. METHODS: Clinical data were collected from hospital charts of patients with severe sepsis and septic shock admitted to a mixed intensive care unit from November 2003 to February 2004. The duration of organ dysfunction prior to diagnosis was correlated with mortality. Results were considered significant if p